1994
DOI: 10.1111/j.1365-2036.1994.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and retrograde colonic spread of budesonide enemas in patients with distal ulcerative colitis

Abstract: Methods:The retrograde spread of two budesonide enema formulations with different viscosities was investigated. The study design was open, randomized and two-period crossover. Three female and two male patients (age range: 35-45 years) with distal ulcerative colitis or proctitis participated. Both enema formulations contained a dose of 2 mg budesonide/ 100 mL. An unabsorbable radioactive marker ( 99mTc-labelled human serum albumin microcolloid) was added to the enema just before administration. All doses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Also, the rate and extent of spreading was more variable with the latter formulations. The rapid evaporation of water from topical formulations influences the spreadability and results in an uneven topical dose within the treated area (Nyman-Pantelidis et al, 1994). The formulations also must be spread quickly and at multiple sites to ensure correct dosage.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the rate and extent of spreading was more variable with the latter formulations. The rapid evaporation of water from topical formulations influences the spreadability and results in an uneven topical dose within the treated area (Nyman-Pantelidis et al, 1994). The formulations also must be spread quickly and at multiple sites to ensure correct dosage.…”
Section: Resultsmentioning
confidence: 99%
“…Together with controlled-ileal-release capsules and pHmodified release capsules, a budesonide prodrug (budesonide-beta-D-glucuronide) [11] has been tested to allow a homogeneous release of the drug along the entire colon. Furthermore, budesonide enema and foam seem to be able to reach splenic flexure and sigmoid colon after rectal application [12,33]. Food had little influence over systemic availability, with following peak plasma concentrations of budesonide administered in controlled ileal release capsules being achieved at the same dose regardless of prandial status in patients with CD [14].…”
Section: Pharmacology Of Budesonidementioning
confidence: 97%
“…The first study (21) showed that budesonide does not accumulate in the human body after 4 weeks of treatment; also, mean plasma cortisol values did not change during this period of time. The second study (16) showed that a low viscosity formulation of budesonide had an improved capacity to reach the more proximal parts of the colon, reaching the splenic flexure in 15 minutes. In the third study (22), a dose of 2 mg/day showed the same efficacy as the 4 mg/day dosage, but with less plasma cortisol suppression.…”
Section: Studies Of Budesonide In Ulcerative Colitis Topical Budesonimentioning
confidence: 99%
“…This explains the mere 10% of oral bio-availability and the low systemic action of budesonide. When administered as an enema to humans, budesonide reaches the splenic flexure (16). Its bioavailability then averages 15% in patients with UC.…”
Section: Budesonide Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation